Scattered accumulation hotspots of macro-litter on the seafloor: Insights for mitigation actions. (1st January 2022) - Cau, Alessandro; Franceschini, Simone; Moccia, Davide; Gorule, Pankaj A.; Agus, Blondine; Bellodi, Andrea; Cannas, Rita; Carugati, Laura; Cuccu, Danila; Dessì, Claudia; Marongiu, Martina F.; Melis, Riccardo; et al.
Abstract: Marine litter is an ever-increasing problem that demands immediate reduction plans and mitigation actions that should act synergically to efficiently meet ambitious goals. Since the seafloor has been recognized as the major sink for marine debris, the study of litter accumulation dynamics represent a fundamental tool to evaluate possible removal actions. We analysed a 7 years (2013–2019) standardized data series collected along Sardinian fishing grounds through MEDiterranean International Trawl Survey, for which estimates of density and weight of seafloor macro-litter were calculated for over 707 hauls. Results show the absence of any temporal trend in seafloor macro-litter density and weight, but rather indicate a spatial and bathymetric segregation of different litter categories. Our data showed how different sources and physical features of macro-litter items ( i.e., plastic and fishing gear, rubber, glass, metals, and cloth) led to spatially segregated accumulation hotspots. We also point out here how the identification of seafloor macro-litter hotspots using aggregated data that include plastic items could obscure the identification of other segregated but yet relevant hotspots of other macro-litter categories accumulated in the marine environment. These hotspots often occurred at shallower depths and closer to coastlines, thus representing potential spots where eventual future litter removal action could be prioritized. Highlights: We investigated temporal trends in seafloor macro-litter abundance in 7 years study. Macro-litter abundance and density did not show any temporal trend. Accumulation hotspots showed a segregated distribution according to litter typologies. More accessible areas for mitigation actions have been identified. Aggregated data may blur the identification of other minor accumulation hotspots.